The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5194/hessd-12-6945-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Green and blue water footprint reduction in irrigated agriculture: effect of irrigation techniques, irrigation strategies and mulching

Abstract: Abstract. Consumptive water footprint (WF) reduction in irrigated crop production is essential given the increasing competition for fresh water. This study explores the effect of three management practices on the soil water balance and plant growth, specifically on evapotranspiration (ET) and yield (Y) and thus the consumptive WF of crops (ET/Y). The management practices are: four irrigation techniques (furrow, sprinkler, drip and subsurface drip (SSD)); four irrigation strategies (full (FI), deficit (DI), sup… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…CET c , CE spg , and CE r are the seasonal cumulative crop evapotranspiration, cumulative effective seepage, and cumulative effective rainfall contribution, respectively [ Orang et al ., ]. CUP+ does not distinguish between E and T and does not incorporate capillary rise, unlike other ET models used to determine high‐resolution water footprints [ Chukalla et al ., ; Zhuo et al ., ]. However, depths to the water table are considerable in the Central Valley, so capillary rise is negligible for crop growth in this region.…”
Section: Methodsmentioning
confidence: 99%
“…CET c , CE spg , and CE r are the seasonal cumulative crop evapotranspiration, cumulative effective seepage, and cumulative effective rainfall contribution, respectively [ Orang et al ., ]. CUP+ does not distinguish between E and T and does not incorporate capillary rise, unlike other ET models used to determine high‐resolution water footprints [ Chukalla et al ., ; Zhuo et al ., ]. However, depths to the water table are considerable in the Central Valley, so capillary rise is negligible for crop growth in this region.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the fact that more than 90% of freshwater resources are consumed in the agricultural sector, one of the main strategies to alleviate water scarcity is to reduce agricultural water consumption (Chukalla et al ., ). Both rainfed and irrigated farming systems are common in Iran.…”
Section: Introductionmentioning
confidence: 97%
“…The concept of WF was first introduced by Hoekstra () and has been used in many studies in the field of freshwater resources management (Gerbens‐Leenes et al ., ; Aldaya and Hoekstra, ; Tian, ; Ababaei and Ramezani Etedali, ; Antonelli and Sartori, ; Chukalla et al ., ; Pahlow et al ., ; Schyns et al ., ; Wang et al ., ; Zhuo et al ., ; Ababaei and Ramezani Etedali, ). The WF is defined as the volume of consumed or polluted water for producing a product and it is calculated over its whole production chain.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Virtual water footprint (WF) and virtual water (VW) trade are promising concepts for sustainable management of groundwater and surface water resources, when there is no new source to meet the ever‐growing demand for water, especially in dry and semi‐dry regions (Gleick, ; Postel, ; Norse, ; Yang et al ., ; World Water Assessment Programme (WWAP), ; Mekonnen and Hoekstra, ). It has been suggested in the literature that VW trading can be an approach for saving water resources and to achieve water security at the regional, national and international level (Allan, ; Hoekstra, ; De Fraiture et al, ; Oki and Kanae, ; Yang et al ., ; Chapagain et al, ; Liu et al, ; Gerbens‐Leenes et al, ; Aldaya and Hoekstra, ; Tian, ; Antonelli and Sartori, ; Chukalla et al, ). A study on VW trade for produced and consumed products in three states New Jersey, Maryland and Delaware in the USA showed that water consumption would be reduced by 35% through VW trade management (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%